Formation of a long-lived electron-transfer state in mesoporous silica-alumina composites enhances photocatalytic oxygenation reactivity - Fukuzumi, Shunichi (National Academy of Sciences, 2012)
A simple donor-acceptor linked dyad, 9-mesityl-10-methylacridinium ion (Acr(+)-Mes) was incorporated into nanosized mesoporous silica-alumina to form a composite, which in acetonitrile is highly dispersed. In this medium, upon visible light irradiation, the formation of an extremely long-lived electron-transfer state (Acr(•)-Mes(•+)) was confirmed by EPR and laser flash photolysis spectroscopic methods. The composite of Acr(+)-Mes-incorporated mesoporous silica-alumina with an added copper complex [(tmpa)Cu(II)][Image: see text] (tmpa = tris(2-pyridylmethyl)amine) acts as an efficient and robust photocatalyst for the selective oxygenation of p-xylene by molecular oxygen to produce p-tolualdehyde and hydrogen peroxide. Thus, incorporation of Acr(+)-Mes into nanosized mesoporous silica-alumina combined with an O(2)-reduction catalyst ([(tmpa)Cu(II)](2+)) provides a promising method in the development of efficient and robust organic photocatalysts for substrate oxygenation by dioxygen, the ultimate environmentally benign oxidant.